1988
DOI: 10.2169/internalmedicine1962.27.79
|View full text |Cite
|
Sign up to set email alerts
|

The papilla of vater emptying into the duodenal bulb. Report of two cases.

Abstract: Wehave identified two cases in which anomalous papilla of Vater was found emptying into the duodenal bulb. In both instances, bile outflow from the papilla was confirmed endoscopically and endoscopic retrograde cholangiopancreaticography (ERCP) was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 3 publications
0
30
0
Order By: Relevance
“…In fact, diseases related with the biliary system are reported frequently in patients with ectopic CBD opening [2][3][4]9,[11][12][13][14][15][16][17][18]. In this study, CBD dilatation was found in 94% of the cases with or without intrahepatic biliary dilatation.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In fact, diseases related with the biliary system are reported frequently in patients with ectopic CBD opening [2][3][4]9,[11][12][13][14][15][16][17][18]. In this study, CBD dilatation was found in 94% of the cases with or without intrahepatic biliary dilatation.…”
Section: Discussionmentioning
confidence: 61%
“…In another large series, the pancreatic canal was visualized in one of the eight patients and was opened to the papillary orifice in the bulbus, which also appeared normal [11]. The pancreatic channels of 11 patients who had CBD opening into the duodenal bulb were visualized in the literature [4,9,11,15]. Acute pancreatitis was diagnosed in only one case (there was no finding supporting pancreatitis other than elevated amylase level in this case, who was also a heavy alcohol user) [15].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As noted by previous authors, ectopic drainage of the common bile duct may be located along a line extending from the stomach to the fourth part of the duodenum [1][2][3][4][5] . The frequency of this anomaly fluctuates between 0% and 13% [1,6] .…”
Section: Discussionmentioning
confidence: 99%
“…On rare occasions it may be found in other sites, along a line extending from the stomach to the fourth part of the duodenum [1][2][3][4][5] . Here we present a case of periampullary carcinoma combined with ectopic opening of the Vater's ampulla into the fourth part of the duodenum and a low confluence of the cystic duct into the common bile duct.…”
Section: Introductionmentioning
confidence: 99%